Thermoplasmatales and sulfur‑oxidizing bacteria dominate the microbial community at the surface water of a CO2‑rich hydrothermal spring located in Tenorio Volcano National Park, Costa Rica - Arce-Rodríguez, Alejandro (2019)
Here we report the chemical and microbial characterization of the surface water of a CO2-rich hydrothermal vent known in Costa Rica as Borbollones, located at Tenorio Volcano National Park. The Borbollones showed a temperature surrounding 60 °C, a pH of 2.4 and the gas released has a composition of ~ 97% CO2, ~ 0.07% H2S, ~ 2.3% N2 and ~ 0.12% CH4. Other chemical species such as sulfate and iron were found at high levels with respect to typical fresh water bodies. Analysis by 16S rRNA gene metabarcoding revealed that in Borbollones predominates an archaeon from the order Thermoplasmatales and one bacterium from the genus Sulfurimonas. Other sulfur- (genera Thiomonas, Acidithiobacillus, Sulfuriferula, and Sulfuricurvum) and iron-oxidizing bacteria (genera Sideroxydans, Gallionella, and Ferrovum) were identified. Our results show that CO2- influenced surface water of Borbollones contains microorganisms that are usually found in acid rock drainage environments or sulfur-rich hydrothermal vents. To our knowledge, this is the first microbiological characterization of a CO2- dominated hydrothermal spring from Central America and expands our understanding of those extreme ecosystems.